PENGARUH KOMBINASI AMPAS TEH DAN LERI PADA SIFAT KIMIA ULTISOL TERHADAP PRODUKSI TANAMAN CABAI RAWIT - Muhammad Helmy Abdillah; Maimunah Maimunah (ZIRAA'AH MAJALAH ILMIAH PERTANIAN, 2021)
Chili is a horticultural commodity that has high economic value, one of the leading national vegetable commodities, and has high competitiveness, so its availability must be increased continuously. Production of Cayanne Pepper can be optimized in various ways such as planting fertile and healthy land, can be planting Cayenne Pepper in the home yard, but problems occur when Cayanne Pepper are planted on acid mineral soils such as Ultisol which are known to have low organic matter and nutrients. This study tries to utilize household wasted as tea and leri which is combined and applied to Ultisol so that its effect on the soil and yield of Cayanne Pepper plants can be increased. The design model used in this research is a Completely Randomized Design Factorial consisting of two factors. The first factor is tea wasted (factor T) with 4 levels, as T20 (tea waste 20 g), T40 (tea waste 40 g), T60 (tea waste 60), and T80 (tea waste 80 g). The second factor is the leri water (factor L) with 4 levels, as L50 (leri 50 ml), L100 (leri 100 ml), T150 (leri 150 ml) and L200 (leri 200 ml) so there are 16 combinations of treatments with 3 replications. Observations in the research identification of N-total, P2O5, K2O, total chlorophyll, the weight of fresh fruit, the quantity of fruits, dry weight of plants. The results show that the treatment of the combination of tea wasted and leri water has a positive effect on soil chemical so that it affects the yield of Cayanne Pepper plants.